Mechanical and Microwave Absorption Properties of Exfoliated Graphite and Manganese Ferrite Nanoparticles on Polyvinylidene Fluoride Thin Films - Thamil Amudhu LEKKAIYAN BASKARAN; Vimal Samsingh RAMALINGAM; Esther Florence SUNDARSINGH; Arun Prakash CHANDRAN (Medžiagotyra)
This study presents a simple and efficient method for the development of thin polymer composite films for use in absorbing electromagnetic waves at X-band frequencies. The thin film composites were fabricated by solution casting technique by incorporating the exfoliated graphite, and manganese ferrite nanoparticles into the polyvinylidene fluoride matrix. The composite film consisting of both 3 wt.% of MnFe2O4 and exfoliated graphite/PVDF showed better absorption properties and achieved a minimum reflection loss of –30.54 at 9.62 GHz in the 8 – 12 GHz frequency range. This synergistic effect of the film was attributed to its β-phase formation, multiple-reflection-absorption effect, and the conduction of fillers at their interfaces. Finally, the mechanical and absorption characteristics of the fabricated thin film composites were also investigated. The results indicated that these composite films hold potential for use in microwave absorption applications in the X band.